Analysis of the Electrical Properties of Graphene Oxide from Bamboo Betung Synthesized by the Modified Hummers Method - Putry, Reka Anisha Reza; Ramli, Ramli; Ratnawulan, Ratnawulan; Hidayat, Rahmat (Journal of Experimental and Applied Physics, 2023)
The purpose of this study is to know the capacitance and conductivity  of graphene oxide made from betung bamboo. Betung bamboo was synthesized using modified hummers method. The carbonization procedure, which will be the control variable in this study, will be carried out in the first stage at four different temperatures for an hour: 300°C, 350°C, 400°C, and 450°C. The results are identified by the initials GO300, GO350, GO400, and GO450. The samples were then characterized using the XRD (X-Ray Diffraction), SEM (Scanning Electron Microscope), FTIR (Fourier Transform Infrared), and LCR Meter instruments. At a temperature of 400 °C, the LCR Meter measured the greatest conductivity and conductance values, with values of 5.43x10-6 S/cm for conductivity and 5.66x10-7 F/m2 for area capacitance. And according to the average conductivity and conductance values, this graphene oxide is situated in the region of semiconductor materials conductivity values.